Investigation of the effects of in ovo taurine injection on hatching characteristics and stress reduction potential - Baykalir, Yasin; Simsek, Ulku Gulcihan; Seker, Ibrahim; Koseman, Abdurrahman; Gul, Burcu; Eroglu, Mehmet; Demir, Pelin (Wiley, 2024)
BackgroundIn ovo application is the process of administering some nutrients or components into the egg. The main purpose of this application is to ensure that some nutrients are provided to chicks with a short incubation period. Few studies were conducted with taurine in fertile eggs; especially, no observation of hatchability and chick quality has been found. In addition, taurine has an anti-stress impact that fights oxidative factors.ObjectiveTo assess the hatchability and chick quality after in ovo taurine administration. To determine the stress that may occur as a result of in ovo application and whether taurine has a stress-reducing effect.MethodsA total of 1200 fertile eggs from a 34-week-old broiler breeder (Ross 308) flock were categorized into 4 groups with 75 eggs per replicate: control (uninjected), taurine group (0.30 mL dissolved taurine in distilled water), sham control (sterile distilled water) and perforation (eggs perforated and then waxed). On day 14 of incubation, an in ovo injection was administered to the albumen. Data on hatching parameters and hepatic HSP70 levels were obtained using relevant formulas and western blotting, respectively.ResultsControl chicks exhibited higher hatchability than other groups, with the taurine group showing the lowest hatchability. The HSP70 levels were the highest in the perforation group compared to the control group. An increase of 21.37% in the taurine group and 83.45% in the sham control group was observed compared to the control group.ConclusionsThe findings suggest that in ovo application may induce increased stress, whereas taurine may have positive effects in mitigating the stress caused by in ovo application. In ovo application causes stress. In ovo taurine administration showed a stress reduction effect the stress caused by in ovo application. Control chicks exhibited higher hatchability. image
Keywords: hatching; HSP70; in ovo; stress; taurine